Pre-skills of reading and writing in children with developmental language disorder and children with typical language development - Mirjana Korlaet; Mile Vuković; Jelena Tešić (Биомедицинска истраживања, 2023)
Introduction: In addition to the development of spoken language, typical intellectual abilities, preservation of the senses of hearing and sight, phonological awareness and the ability of graphomotor expression are necessary for mastering the skills of reading and writing. With this in mind, the aim of this research is to determine the level of phonological awareness and the ability of graphomotor expression in children with developmental language disorder (DLD) and children with typical language development (TLD). Methods: The sample consisted of 46 children aged five to seven years, who were divided into two groups based on the status of speech and language abilities. The first group consisted of 23 children with DLD, and the second of 23 children with TLD. The FONT test was used to assess phonological awareness, and the Prediction Test for Dysgraphia was used to assess graphomotor abilities. Results: The results of the research show that children with DLD performed poorly on phonological awareness tasks compared to TLD children. Age proved to be a significant factor in differences in the development of phonological awareness. Achievements on the Prediction Test for Dysgraphia show that children with DLD have almost twice the weaker ability of graphomotor expression compared to TLD children. Furthermore, the research results show that there are significant differences in the level of development of graphomotor skills between children of different ages. Also, no significant difference in achievements on the Prediction Test for Dysgraphia or on the FONT test has been found in relation to gender. Conclusion: Children with developmental language disorder had significantly lower achievements on the phonological awareness test and the Prediction Test for Dysgraphia compared to children with typical language development.
Keywords: gross motor ability; phonological awareness; developmental language disorder; typical language development; pre-skills of reading and writing